The icebound land - Flanagan, John (John Anthony) (New York : Philomel Books, 2007)
Chasing the Skandian slave-traders who kidnapped Will and Evanlyn, Ranger Halt and warrior student Horace find themselves in the frozen northern islands, where they battle a ruthless black-clad knight as they attempt to rescue their friends.
Keywords: Heroes -- Juvenile fiction; Kidnapping -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Fantasy fiction